2002
DOI: 10.1002/cncr.10705
|View full text |Cite
|
Sign up to set email alerts
|

Clinical importance of serum interleukin‐18 and nitric oxide activities in breast carcinoma patients

Abstract: BACKGROUND Interleukin‐18 (IL‐18) is a novel immunoregulatory cytokine that was known previously as interferon‐γ–inducing factor. IL‐18 levels can be used as a serum indicator for monitoring the clinical course of patients with hematologic malignancies and gastric carcinoma. Nitric oxide (NO) is a pleiotropic molecule that participates in the multistep processing of carcinogenesis. METHODS In the current study, we measured serum IL‐18 and nitrate and nitrite levels in 38 metastatic and 26 nonmetastatic breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
0
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 30 publications
4
50
0
4
Order By: Relevance
“…Still, IL-18 may presumably be an important marker in the progression of breast cancer, [6] as serum IL-18 levels in breast cancer patients who developed bone metastases were found to be significantly higher in several studies. [7,8] In light of these results, the usefulness of serum IL-18 as a marker of the potential development of bone metastases in breast cancer patients was presently investigated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Still, IL-18 may presumably be an important marker in the progression of breast cancer, [6] as serum IL-18 levels in breast cancer patients who developed bone metastases were found to be significantly higher in several studies. [7,8] In light of these results, the usefulness of serum IL-18 as a marker of the potential development of bone metastases in breast cancer patients was presently investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study conducted by Günel et al in 2002, serum IL-18 levels in the metastatic and nonmetastatic groups were found to be higher than those of the healthy group, while serum IL-18 levels of the group with bone metastases were higher than those of the nonmetastatic group. [7] However, in several studies, some performed by Günel et al, breast cancer patients with metastases in other organs constituted a separate study group. Still, serum IL-18 levels of breast cancer patients with bone metastases were statistically significantly higher, compared to those of breast cancer patients with other organ metastases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can raise the immune protection against cancer cells by energizing and stimulating the IFN-γ creation and therefore has a key role in Th1 response [8]. It has been made known that IL-18 has a major role in the progression of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…IL-18 can organize both adaptive and innate immune responses during its impacts on natural killer (NK) cells, dendritic cells, monocytes, B-cells, and T-cells [8]. It can increase the immune resistance toward tumor cells by energizing and stimulating the interferon (IFN-γ) production and therefore has a key role in Th1 response [8].…”
Section: Introductionmentioning
confidence: 99%